Determinants for tuberculosis in HIV-infected adults in Northwest Ethiopia : a multicentre case–control study - Alemu, Yihun Mulugeta (2018)
Objective: The objective of this study was to identify determinants for tuberculosis (TB) among HIV-infected adults in Northwest Ethiopia. Design: Case–control study. Setting: Three hospitals and 10 health centres in Northwest Ethiopia. Participants: A total of 446 individuals consented to participate in the study (150 cases and 296 controls). Cases were HIV-infected adults diagnosed with active TB, and controls were HIV-infected adults without active TB. Main outcome measure: The link between TB and determinants was assessed using logistic regression. Determinants were categorised as sociodemographic, host-related, clinical and environmental. Results: Smoking (adjusted OR (AOR) 5.47; 95% CI 2.26 to 13.22), presence of a TB patient in the family (AOR 2.66; 95% CI 1.25 to 5.66), alcohol consumption (AOR 2.49; 95% CI 1.29 to 4.80) and chewing khat (AOR 2.22; 95% CI 1.11 to 4.41) were independent determinants for increased occurrence of TB. Highly active antiretroviral therapy (HAART) (AOR 0.25; 95% CI 0.13 to 0.51), isoniazid preventive therapy (IPT) (AOR 0.22; 95% CI 0.11 to 0.41) and cotrimoxazole preventive therapy (AOR 0.32; 95% CI 0.19 to 0.55) had a protective effect against TB. Conclusions: HIV-infected adults with substance abuse (tobacco smoking, khat chewing and alcohol) should be prioritised for TB screening. This study reaffirmed that HAART and IPT are some of the best strategies for reducing TB occurrence in HIV-infected adults. These findings provide impetus to intensify tracing of TB household contacts.